SAT0277 Clinical Response in Early Psoriatic Arthritis may be Predicted by Rapid Reduction of a Semiquantitative Ultrasound Synovitis Score. (23rd January 2014) - Nigg, A. P.; Malchus, A. M.; Gruenke, M.; Witt, M.; Prinz, J.; Schulze-Koops, H.
Abstract : Background: Accurate monitoring of disease activity in early PsA is limited by the potential underestimation of inflammation by clinical examination and the absence of disease-specific biochemical markers. Therefore, sensitive and reliable diagnostic modalities enabling visualization of early inflammatory changes are required as a diagnostic tool and for monitoring the response to therapy. Objectives: The aims of this longitudinal study were to analyse differences of a semiquantitative ultrasound score between clinical responers and non-responders during treatment of early PsA. Furthermore we tested if a rapid reduction of ultrasound activity 3 months after initiation of DMARD treatment allows prediction of long term disease outcome defined by MDA criteria (minimal disease activity). Methods: 51 patients were eligible for study inclusion, to date 18 patients have completed a 3- and 6-month follow-up visits. Patients were evaluated by ultrasound (US) and clinically at baseline and after 3, 6 and 12 months. In each patient a total of 56 joints were examined by US. Grey-Scale (GS) and power doppler (PD) US findings were scored separately on a 0-3 semi-quantitative scale as previously described. The total US synovitis score was calculated by adding the scores in the GSUS and PDUS modes for all joints examined. Clinical assessment included a composite ACR joint count of 68 tender and 66 swollen joints, visual analog scale (VAS) for disease activity (patient and physician), VAS for pain, DAS-28-CRP, Leeds dactylitis instrument, MASES, HAQ, CRP, ESR and demographic data. Treatment was initiated and modified according to the clinical decision of the treating rheumatologist and dermatologist in agreement with international recommendations. Criteria for MDA (minimal disease activity in PsA, Coates L. et al. Ann Rheum Dis 2010) were defined for each follow-up period. Results: Improvement of the semiquantitative synovits ultrasound score as well as improvement of clinical and laboratory parameters after 3 months of treatment was associated with fulfillment of MDA criteria at 6-month follow-up-Visit (OR, odds ratio): total US synovitis score (OR=9.0), PDUS sub-score (OR=0.77), TJC68 (OR=9.0), SJC66 (OR=2.4), CRP (OR=infinite), HAQ (OR=3.38), PGA (OR=2.4). In patients fulfilling the MDA criteria (6-months-follow up) the mean percentage change of the total US synovitis score after 3 month was -28.4% whereas non-responders showed a mean increase of the score by 31.9%. Conclusions: Changes in the GSUS and PDUS scores allow discrimination between clinical responders and non-responders (defined by minmal disease activity criteria, MDA). Changes of a semiquantitative ultrasound synovitis score after 3 months of DMARD treatment are strongly associated with the overall clinical activity after 6 months. The response measured by ultrasound may therefore be predictive for a favourable long-term clinical outcome and may allow early identification of patients with poor prognosis who might benefit from treatment with biologics. Disclosure of Interest: None Declared